The Effect of ESG Score, Financial Performance, and Macroeconomics on Stock Returns during the Pandemic Era in Indonesia - Trisnowati, Yanuar; Achsani, Noer A.; Sembel, Roy; Andati, Trias (International Journal of Energy Economics and Policy, 2022)
This study analyzed the effect of ESG Score, financial performance, and macroeconomic variables on stock returns by using the Covid-19 pandemic period in Indonesia as a dummy variable. The sample was 26 companies listed on the Sri-Kehati and IDX ESG Leaders indexes between 2015 and 2020. Furthermore, the stepwise regression method was used, and the secondary data used were sourced from financial reports and Indonesian macroeconomic data. The first step results showed Debt to Equity Ratio has a positive and significant effect on stock returns, while the ESG Score, Return on Assets, and Firm Size do not have an effect. The results of the second step showed the model is simultaneously not feasible and the macroeconomic variables need to be removed. Therefore, it was concluded that a good model is one with ESG Score and financial performance variables that affect stock return, while macroeconomic variables need to be excluded from the model.